Making Simple Repairs: Clogged Drains - Mary N. Harrison (EDIS)
Clogged drains can create a problem. However, a few simple precautions will help you to keep the drains open and in good working condition. This document is FCS5234-05 one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date: May 2002. Revised: December 2005.